Percepção de profissionais sobre o núcleo interno de regulação de um hospital universitário - Machado, Rosângela Marques (2021)
Seeking to ensure the population's equitable access to health services, comprehensive care and adjust the existing care offer to the specific needs of the population in a rational, timely and orderly manner, the Access Regulation Centers were created, including the implementation of the Center Internal Regulation (NIR) in hospitals. Which has an impact on safe bed occupancy rates, minimizing the risk of overcrowding in emergencies. This study aims to understand the perception of nurses and physicians, working in a surgical unit of a university hospital, about the NIR. This is a descriptive, exploratory field research with a qualitative approach. The research was carried out in a university hospital located in the interior of the State of Rio Grande do Sul. The study participants were medical professionals and nurses working in the surgical clinic unit of the aforementioned institution. Fourteen professionals participated in the study, nine nurses and five physicians. Data collection took place through semi-structured interviews, from January to March 2021. The collected data were transcribed and analyzed using Bardin's content analysis. It is noteworthy that the entire research was governed by Resolution 466/2012, respecting the ethical aspects of research carried out with human beings. Data analysis allowed the construction of two subcategories: knowledge of professionals from a surgical clinic of a University Hospital about the NIR; and strengths and weaknesses of the NIR from the perspective of professionals in a surgical clinic. Thus, the study enabled the construction of knowledge about the insertion of the NIR in the hospital setting, recognizing its contributions, difficulties and necessary advances from the perspective of the care team, and the insertion of nursing in this area.